2018
DOI: 10.1021/acs.jpclett.8b02311
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Cooling of Surface-Modified Gold Nanorods upon Pulsed Infrared Photoexcitation

Abstract: Transient infrared emissions of gold nanorods capped with various materials (AuNR@X, X = CTAB, PSS, mPEG, and SiO) upon ∼70-μs pulsed 1064 nm excitation of their longitudinal surface plasmonic bands were collected with a time-resolved step-scan Fourier-transform spectrometer. Comparing the observed emission contours with the blackbody radiation spectra revealed that parts of the additional emission intensity at low wavenumbers (1300-1000 cm) were attributed to the vibrational modes of the capping materials, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The data acquisition followed previous reports [13,14] with slight modifications. The AuNR@X-SiO 2 sample dried on the CaF 2 window mentioned in Section 2.1.5 was mounted at the focal point of the parabolic mirror for collecting the external emission at the side of the interferometer.…”
Section: Time-resolved Infrared Emission Spectroscopymentioning
confidence: 99%
See 4 more Smart Citations
“…The data acquisition followed previous reports [13,14] with slight modifications. The AuNR@X-SiO 2 sample dried on the CaF 2 window mentioned in Section 2.1.5 was mounted at the focal point of the parabolic mirror for collecting the external emission at the side of the interferometer.…”
Section: Time-resolved Infrared Emission Spectroscopymentioning
confidence: 99%
“…Porous silica-coated plasmonic metal nanoparticles have numerous advantages in dispersivity and in chemical and thermal stability. [12] Recent studies have shown that optically-heated gold nanostructures are capable of radiatively relaxing energy via the thermal emission of the infrared photons [13,14] rather than thermal conduction. The thermalization kinetics depends on the types of the capping materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations